Modes of being and forms of predication - DESCOLA, PHILIPPE (HAU journal of ethnographic theory, 2014)
Notions like “nature” or “culture” do not denote a universal reality but a particular way, devised by the Moderns, of carving ontological domains in the texture of things. Other civilizations have devised different ways of detecting qualities among existents, resulting in other forms of organizing continuity and discontinuity between humans and nonhumans, of aggregating beings in collectives, of defining who or what is capable of agency and knowledge. The paper emphasizes that these processes of ontological predication are not “worldviews” but, properly speaking, styles of worlding. Ontology is taken here as designating a more elementary analytical level to study worlding than the one anthropology usually calls for. It is at this level, where basic inferences are made about the kinds of beings that exist and how they relate to each other, that anthropology can best fulfill its mission to account for how worlds are composed.